IMPLEMENTATION OF THE DEMONSTRATION AND DIALOGUE METHODS IN TEACHING PRAYER: ANALYSIS OF HADITH - Siti Nuraini; Syabuddin (STAI Nusantara Kota Banda Aceh, 2026)
This study aims to analyse the implementation of demonstration and dialogue methods in teaching prayer based on the hadith of the Prophet Muhammad SAW. Prayer, as a major act of worship, requires a deep understanding of both theory and practice. The demonstration method is important because it emphasises the skills involved in the movements of prayer, while the dialogue method emphasises understanding the meaning and appreciation of worship through questions and answers and discussion. This study uses a qualitative literature approach by examining hadiths about teaching prayer, especially the hadith about the Prophet's prayer: ‘Shallu kama ra'aitumuni usalli’ (pray as you see me pray). The results of the study show that the integration of demonstration and dialogue methods in prayer learning can improve the psychomotor, cognitive, and affective competencies of students in a balanced manner.